1987
DOI: 10.24266/0738-2898-5.4.163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Planting Depth on Growth of Young Apple Trees

Abstract: Shallow planted trees of ‘Delicious’ apple (Malus domestica Borkh.) on Malling 7A (M 7A) and Malling-Merton 111 (MM 111) rootstock were smaller in the 5th year following planting and had higher bloom densities than deep-planted trees. Trees on MM 111 also had more fruit per cross sectional area when shallow planted. Deep planted trees of MM 111 had greater depth to the first root. No differences were observed in degree of lean of either rootstock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…from a container (Bryan et al 2010) and Corylus colurna L. from a field nursery (Day and Harris 2008), landscape planting depth had a negligible effect on magnolia trunk growth and height growth in the 68 months after planting (Table 4). In contrast, other researchers (Lyons et al 1987;Arnold et al 2007) found reduced trunk diameter growth with increasing landscape planting depth when installing containergrown trees. However, landscape planting depth affected root system radius and root to shoot spread ratio (Table 4).…”
Section: Landscape Planting Depthmentioning
confidence: 82%
See 4 more Smart Citations
“…from a container (Bryan et al 2010) and Corylus colurna L. from a field nursery (Day and Harris 2008), landscape planting depth had a negligible effect on magnolia trunk growth and height growth in the 68 months after planting (Table 4). In contrast, other researchers (Lyons et al 1987;Arnold et al 2007) found reduced trunk diameter growth with increasing landscape planting depth when installing containergrown trees. However, landscape planting depth affected root system radius and root to shoot spread ratio (Table 4).…”
Section: Landscape Planting Depthmentioning
confidence: 82%
“…In apparent contrast, certain species capable of generating adventitious roots along the buried stem when planted into field soil from propagation containers (Schwan 1994) perform best when planted a few cm deep. Young seedling-sized trees of those taxa can continue forming adventitious roots after planting-a capacity often lost among older trees planted from shade tree nurseries (Lyons et al 1987).…”
Section: Nursery Planting Depthmentioning
confidence: 99%
See 3 more Smart Citations